Fostering A Moderate Attitude in Sufi-Based Pesantren Culture - Hasan, Moch. Sya'roni; Mujahidin; Azizah, Mar’atul; Solechan (At-tadzkir: Islamic Education Journal, 2024)
This research explores the internalization of Sufism values in forming an attitude of religious moderation in the Thoriqoh Syadziliyah Al Masudiyah Jombang congregation amidst increasing radicalism. Using a qualitative case study approach, data was collected through participant observation, in-depth interviews, and documentation studies, then analyzed using Miles and Huberman's interactive model. The results show that the internalization of Sufism values such as asceticism, tawakkal, sincerity, patience, gratitude, love, willingness, tolerance, and non-violence is carried out through the recitation of Selapanan Ahad Legi with active learning methods involving the congregation's cognitive, affective, and psychomotor domains. As a result, the congregation developed a moderate attitude toward religion, reflected in a simple lifestyle, optimism, sincere quality of worship, strong fighting power, not being easily provoked, gratitude, love for others, and tolerance of diversity. Further research is recommended to examine the effectiveness of internalizing Sufism values in different age groups or social backgrounds and its impact on community social cohesion.